Territorial cohesion and regional development - case of Bosnia and Herzegovina - Jasmina Osmankovic; Rabija Somun (European Regional Science Association (ERSA), 2010)
Territorial cohesion and regional development - case of Bosnia and Herzegovina In paper we analyzed territorial cohesion and regional development in Bosnia and Herzegovina from 1995 to 2010. In the context this theme we analyzed convergence and disproportional into Bosnia and Herzegovina during the postwar period. We used relevant statistical methods. We focus on demographic data and standard macroeconomic data (gross domestic product, gross domestic product per capita, employment rate, unemployment rate, population rate) on local, cantonal, entities and national level fro relevant statistical offices (Statistical agencies for Bosnia and Herzegovina, Federal Office of Statistics, etc.) We hope that this result would be useful in context discussion about new territorial organization Bosnia and Herzegovina.
Keywords: 330; territorial cohesion; convergence; development; Bosnia and Herzegovina